Evaluation of multifunctional magnesium aluminosilicate materials as novel family of glidants in solid dosage products - Tran, D T; Komínová, P; Kulaviak, L; Zámostný, P (International journal of pharmaceutics, 2021)
The work was aimed at evaluating the efficiency of multifunctional magnesium aluminosilicate materials (MAS) as a novel glidant in solid dosage forms. MAS are known for their very low cohesive interactions and their utilization could avoid the disadvantages associated with conventional glidant usage. Flow properties of several mixtures comprising a model excipient (microcrystalline cellulose) and a glidant were characterized using a powder rheometer FT4. The mixtures were formulated to represent effects of glidant types, various levels of glidant loading, particle size and mixing time on flow properties of the model excipient. Pre-conditioning, shear testing, compressibility, flow energy measurements and an additional tapping test were carried out to monitor flow properties. Mixtures were analyzed employing scanning electron microscopy, using a detector of back-scattered electrons to identify a mechanism of MAS towards improving the mixture flow properties. All studied parameters were found to have substantial effects on mixture flow properties, but the effect of mixing time was much less important compared to mixtures based on traditional glidant. The mechanism of MAS glidant action was found to be different compared to that of traditional one, having less process sensitivity, so that MAS utilization as glidant could be advantageous for the formulation performance.
Keywords: Flow-enhancer; silikáty; pomocné látky; Silicates; Powders; Powder rheology; sloučeniny hliníku; Flow properties; prášky, zásypy, pudry; velikost částic; Magnesium Compounds; sloučeniny hořčíku; Rheology; Glidant; Aluminum Compounds; Particle Size; reologie; Excipients; Powder mixing; Magnesium aluminosilicate